PENGARUH TEKNIK INJEKSI STEROID DENGAN TUNTUNAN ULTRASONOGRAFI TERHADAP LUARAN KLINIS PASIEN CARPAL TUNNEL SYNDROME - Mariana Sutopo,* Yudy Goysal,* David Gunawan Umbas,* Susi Aulina, Louis Kwandou,* Andi Alfian Zainud (Neurona Majalah Kedokteran Neuro Sains, 2018)
INTRODUCTION CARPAL TUNNEL SYNDROME CTS IS THE MOST COMMON ENTRAPMENT NEUROPATHY IN THE UPPER EXTREMITY AND ONE OF THE DISEASES THAT CAUSES DISABILITY THEREBY REDUCING PRODUCTIVITY THIS STUDY PURPOSE IS TO DETERMINE THE EFFECT OF STEROID INJECTION TECHNIQUES WITH AND WITHOUT ULTRASOUND GUIDANCE ON CLINICAL OUTCOMES IN PATIENTS WITH CTS